Note on the cochran Q test - Tate, Merle W; Brown, Sara M (Journal of the American Statistical Association, 1970)
Cochran’s Q test for differences between related-sample percentages or proportions has generally been incorrectly presented in secondary sources. The most common mistake results from failure to recognize that rows containing only 1’s or only 0’s, i.e., only successes or only failures, do not affect the value of Q. The F test, however, is affected by such rows. The probabilities from the χ2 and F approximations are compared with the exact probabilities in three sets of data. A rule of thumb, based on extensive study of the distribution of 0 in small samples, is given as an aid in judging when the χ2 approximation is satisfactory for practical purposes. © Taylor & Francis Group, LLC.
Keywords: dept.mat